A test of information aversion - Jan Christopher Kops; Illia Pasichnichenko (University of Heidelberg, Department of Economics, 2020)
The standard Bayesian model implies that information can never have a negative value. We put this implication to the proof. Our paper provides the first test of the value (positive or negative) of information under uncertainty. We show that the "Bayesian implication" stands in conflict with the information-averse behavior that is revealed in our experiment. This behavior demonstrates that the value of truthful and unambiguous information may indeed be negative. Our findings complement predictions from recent theoretical work in showing that negative value of information correlates with ambiguity aversion. This highlights the importance of counseling for decision-making under uncertainty.
urn:nbn:de:bsz:16-heidok-282444
Keywords: D81; D83; D90; 330; Value of Information; Ambiguity Aversion; Ellsberg paradox; Ellsberg urn